Development of a smoke prediction model for stairways in a multi-storey building - Suhaimi, Nurud Suria (2019)
Multi-storey building in Malaysia has rapid growth rate especially in urban area with high population. During emergency in building fire, smoke could disturb people’s health and vision thus affects the evacuation time. Simple and transparent engineering methods can create opportunities to better understand a complex fire phenomenon and estimate the answer quickly before making decision. Existing methods of calculation can only predict smoke temperature in a single fire compartment and there was a lack of calculation method for multi-storey compartment. The main goal of this study is to develop a new and validated simplified mathematical model to predict the smoke conditions in a multi-storey building specifically in a stairway which used as the only route for rescue and evacuation when fire happens. In this thesis, an experimental setup consisting one fire room adjacent to the vertical shaft fire scenario were simulated using Fire Dynamic Simulator (FDS) version 6.1. Eight (8) independent variable parameters were tested including heat release rate (HRR), enclosure geometry as well as venting opening size to measure the smoke temperature which considered as dependent variable. Three hundred sixty (360) different simulations which study smoke conditions in a room adjacent to a vertical shaft were utilized in statistical analysis to find a constant in mathematical correlation. In order to predict the smoke temperature in a stairway, additional heat loss to the tread boards and landing were also included in developed correlation while calculating. The validity of the mathematical correlation was studied by comparing results from the correlation with numerical simulation and full-scale test data from previous published cases. The predictions with developed correlation were within 32% from the simulation and less than 23% for an experimental full-scale result. Error up to 35% in prediction of smoke temperatures by using developed correlation were accepted and considered good as reported in previous validated work conducted by Nuclear Research Centre (NRC). Sensitivity analysis was conducted to investigate the most affected variables from the correlation model that would impact the smoke temperature in the stairway of multi- storey buildings. From the analysis, it was discovered that vent opening is the most sensitive variables that will affect the smoke temperature in a stairway beside other parameters such as stair and room area, heat release rate and door opening. In conclusion, the derived equation can be used to perform simple calculation for smoke layer temperature in stairway and it is a promising for a faster calculation especially when assessing multiple fire scenarios in a fire safety design. However, further validation studies of the developed model are recommended to be compare with other types of correlation developed from previous researchers.